“Clock dial pattern”, a radiologic clue to neuro-chikungunya diagnosis: a case series - Pedro Henrique Almeida Fraiman; Mariana Freire; Bruno Fernandes; Felipe Palitot; Nathalia Mota; Eduardo Sequerra; Glauco Santos; Mario Emilio Dourado; Clecio de Oliveira Godeiro-Junior; Manuel Moreira-Neto (Arquivos de Neuro-Psiquiatria)
Background Chikungunya is a mosquito-borne disease caused by the chikungunya virus (CHIKV) and can lead to neurological complications in severe cases.